Sclerostin, TNF‐alpha and Interleukin‐18 Correlate and are Together with Klotho Related to Other Growth Factors and Cytokines in Haemodialysis Patients. (January 2016) - Almroth, G.; Lönn, J.; Uhlin, F.; Brudin, L.; Andersson, B.; Hahn‐Zoric, M.
Abstract: Patients with chronic renal failure are known to have renal osteodystrophy (bone disease) and increased calcification of vessels. A new marker of bone disease, sclerostin, the two pro‐inflammatory cytokines tumour necrosis factor‐alpha (TNF‐alpha) and interleukin‐18 (IL‐18), and the fibroblast growth factor‐23 (FGF‐23) receptor‐associated marker Klotho were tested in 84 haemodialysis (HD) patients and in healthy controls. The patients had significantly higher levels of the three former markers than of the controls while Klotho was significantly higher in the controls. Low level, but significant, correlations were observed in the patient group when the levels of these four markers were compared to each other and to those of 5 cytokines and growth factors tested earlier; high‐sensitive CRP (hsCRP), interleukin‐6 (IL‐6), hepatocyte growth factor (HGF), fibroblast growth factor‐23 (FGF‐23) and soluble urokinase plasminogen activator (suPAR). Ln sclerostin correlated positively to Ln hsTNF‐alpha, Ln HGF and Ln suPAR. Ln hsTNF‐alpha correlated positively to Ln sclerostin, Ln hsCRP, Ln IL‐6, Ln FGF‐23, Ln suPAR and Ln IL‐18. Ln IL‐18 correlated positively to Ln suPAR and Ln TNF‐alpha. Ln Klotho correlated negatively to Ln hsCRP but did not correlate to Ln FGF‐23. The markers studied here may be involved in the calcification of vessels seen in HD patients due to a combination of inflammation and bone disease. The mechanisms are still not fully known but may be of importance for future therapeutic possibilities in this group of patients.